OSTEOCHONDROMA IN MANDIBULAR SIMPHYSIS : A CASE REPORT - Teuku Ahmad Arbi (Journal of Syiah Kuala Dentistry Society, 2016)
AbstractOsteochondroma or osteocartilaginous exostosis is one of the most common benign bone tumours. It is frequently observed on the metaphyses of long and flat bones, with no transition to the underlying normal bone. It is rather rare found on the oral and maxillofacial region. This lesion may present in a solitary fashion or as multiple osteochondromas as part of an inherited syndrome that results in disturbances of skeletal growth and development. In the skull, The coronoid process and mandibular condyle are the most commonly affected areas, but very rare in the mandibular symphisis.We present a case of swelling at the lingual anterior mandible region in 24 years old Indonesian female. The swelling was slowly grow, extended to the anterior site. There was no pain and no history of trauma on that region. The patient felt her anterior mandible teeth mobile since 1 year ago. On OPG showed radioluncency on the mandibular symphisis with well defined border. Histopahologic examination result as osteochondroma. We perform en block resection to remove all the tumor. . Two months after surgery, the patient has no complain on operation area.Keywords :osteochondroma, mandibular symphisis, en block resection